ROS-reactive PMS/PC drug delivery system improves new bone formation under diabetic conditions by promoting angiogenesis-osteogenesis coupling via down-regulating NOX2-ROS signalling axis. (December 2022) - Wu, Zimei; Hou, Qiaodan; Chen, Tingting; Jiang, Xingzhu; Wang, Lulu; Xu, Jing; Wang, Lin
Abstract: Reactive oxygen species (ROS) overproduction and oxidative stress increases bone fragility and fracture risk in long-standing diabetes mellitus cases. In this study, a ROS-reactive drug delivery system was prepared to solve this issue by phenyl sulfide mesoporous silica nanoparticles (PMS) loaded with proanthocyanidin (PC). The effect of PMS/PC on new bone formation under diabetic conditions and the underlying mechanism was investigated in-vitro and in-vivo . The results illustrated that the PC was released from the ROS-reactive PMS/PC triggered by peripheral ROS and then eliminated excessive ROS, which achieved dynamic ROS regulation and reached ROS homeostasis finally. Furthermore, we found PMS/PC promoted osteoblastic differentiation in vitro and increased ossification in vivo by promoting the angiogenesis-osteogenesis coupling via down-regulating the expression of nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) to suppress ROS overproduction, preventing vascular oxidative stress. Therefore, our work has proved a therapeutic potential of ROS-reactive PMS/PC in the treatment of diabetic bone disease and indicates excellent prospects of PMS/PC to depress oxidative stress triggered by excessive ROS which is a key pathological factor in many systematic diseases.